THE CORRELATION AMONG HUMAN MILK DONOR, BOTTLE FEEDING, AND BREASTFEEDING STATUS OF MOTHER OF 0-6 MONTHS INFANTS IN YOGYAKARTA, INDONESIA - Widyaningrum, Rachmawati; Wienarno, Elievia; Khofifah, Hesti; Herliyanti, Yuni; Wahyuni, Zly (Fakultas Ilmu Kesehatan, Kedokteran dan Ilmu Alam (FIKKIA), Universitas Airlangga, 2022)
ABSTRACT Background: Human milk donor (HMD) works as temporary support before the mother could breastfeed independently and meet the exclusive breastfeeding (EBF) status on their own. However, caregivers commonly use bottle feeding to give breast milk substitutes for the baby. although it might increase the risk of nipple confusion and disturb the breastfeeding (BF) process. Objectives: this research aimed to explore the relationship between HMD, bottle-feeding, and the BF status of the mother of infants aged 0-6 months in Daerah Istimewa Yogyakarta (DIY). Methods: This is a cross-sectional research using online questionnaires with the link available in social media for four months (December 2020-March 2021), with a total participant number of 123. Data were analyzed using the Kolmogorov-Smirnov and chi-square test. Results: There was no significant correlation between HMD-recipient status and EBF (p=0.080). However, it has a significant relationship with prolonged BF insufficiency (p=0.000; RR=3.214; CI=1.020-4.082). The bottle-feeding utilization was signified as a risk factor for both non-EBF (p=0.020; RR=2.524; CI=1.090-5.844) and prolonged BF insufficiency (p=0.021; RR=2.103; CI=1.073-4.123). Conclusion An approach to use appropriate feeding media through lactation support for the mothers is essential, particularly in HMD practices. ABSTRAK Latar Belakang: Donor Air Susu Ibu (ASI) merupakan salah satu alternatif sementara sebelum ibu dapat menyusui dan mencapai status ASI Esklusif secara mandiri. Namun demikian, dot merupakan media yang sering digunakan oleh pengasuh untuk memberi makan bayi meskipun hal ini dapat meningkatkan resiko bingung puting dan mengganggu proses menyusui. Tujuan: Penelitian ini bertujuan untuk mengetahui hubungan antara Donor ASI, penggunaan dot, dan status menyusui Ibu dari bayi berusia 0-6 bulan di DIY Metode: Penelitian ini merupakan studi cross sectional yang menggunakan kuesioner online dengan link yang tersedia di sosial media selama 4 bulan (Desember 2020- Maret 2021). Jumlah total responden 123 orang. Data diolah menggunakan uji statistik Kolmogorov-smirnov dan chi square. Hasil: Hasil penelitian menunjukkan bahwa tidak ada hubungan yang signifikan antara Donor ASI dan ASI Esklusif (p=008) namun Donor ASI memiliki hubungan dengan keberlanjutan ketidakcukupan ASI (p=0.000; RR=3.214; CI=1.020-4.082). Penggunaan dot memiliki hubungan yang signifikan baik pada status tidak ASI Esklusif (p=0.020; RR=2.524; CI=1.090-5.844) dan keberlanjutan ketidakcukupan ASI (p=0.021; RR=2.103; CI=1.073-4.123). Kesimpulan: Perlu adanya upaya untuk mengedukasi penggunaan media yang tepat untuk pemberian makan bayi melalui proses dukungan menyusui bagi ibu, terutama pada praktik Donor ASI.